Licorice processing involving functions of Evodiae Fructus on liver inflammation and oxidative stress are associated with intestinal mucosal microbiota - Liang, Xuejuan; Tian, Qixue; Chen, Linglong; Zhang, Yanbing; Peng, Yanmei (Frontiers in Microbiology, 2024)
Background This study aimed to investigate the effects of licorice processing of different Evodiae Fructus (EF) specifications on liver inflammation and oxidative stress associated with the intestinal mucosal microbiota. Materials and methods The 25 Kunming mice were divided into control (MCN), raw small-flowered Evodiae Fructus (MRSEF), raw medium-flowered EF (MRMEF), licorice-processed small-flowered EF (MLSEF), and licorice-processed medium-flowered EF (MLSEF) groups. The EF intervention groups were given different specifications of EF extract solutions by gavage. After 21 days, indices of liver inflammation and oxidative stress and intestinal mucosal microbiota were measured in mice. Results Compared with the MCN, malondialdehyde (MDA), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) levels were significantly increased in the MRMEF. Although the trends of oxidative stress and inflammatory indexes in the MLSEF and MLMEF were consistent with those in the raw EF groups, the changes were smaller than those in the raw EF groups. Compared to the raw EF groups, the MLSEF and MLMEF showed closer approximations of metabolic function to the MCN. The abundance of Corynebacterium in MRMEF was significantly lower than that in the MCN, and it was not significantly different from the MCN after licorice processing. The probiotic Candidatus Arthromitus was enriched in the MLSEF. The probiotic Lactobacillus was enriched in the MLMEF. Correlation analysis revealed significant negative correlations between IL-1β, some metabolic functions and Corynebacterium. Conclusion The effects of medium-flowered EF on oxidative stress and inflammatory factors in the liver of mice were stronger than those of small-flowered EF. The licorice processing can reduce this difference by modulating the abundance of Corynebacterium and intestinal mucosal metabolic function.